Omp19 Enables Brucella abortus to Evade the Antimicrobial Activity From Host's Proteolytic Defense System - Pasquevich, Karina A.; Carabajal, Marianela V.; Guaimas, Francisco F.; Bruno, Laura; Roset, Mara S.; Coria, Lorena M.; Rey Serrantes, Diego A.; Comerci, Diego J.; Cassataro, Juliana (Frontiers in Immunology, 2019)
Pathogenic microorganisms confront several proteolytic events in the molecular interplay with their host, highlighting that proteolysis and its regulation play an important role during infection. Microbial inhibitors, along with their target endogenous/exogenous enzymes, may directly affect the host’s defense mechanisms and promote infection. Omp19 is a Brucella spp. conserved lipoprotein anchored by the lipid portion in the Brucella outer membrane. Previous work demonstrated that purified unlipidated Omp19 (U-Omp19) has protease inhibitor activity against gastrointestinal and lysosomal proteases. In this work, we found that a Brucella omp19 deletion mutant is highly attenuated in mice when infecting by the oral route. This attenuation can be explained by bacterial increased susceptibility to host proteases encountered by the bacteria during establishment of infection. Omp19 deletion mutant has a cell division defect when exposed to pancreatic proteases that is linked to cell-cycle arrest in G1-phase, Omp25 degradation on the cell envelope and CtrA accumulation. Moreover, Omp19 deletion mutant is more susceptible to killing by macrophage derived microsomes than wt strain. Preincubation with gastrointestinal proteases led to an increased susceptibility of Omp19 deletion mutant to macrophage intracellular killing. Thus, in this work, we describe for the first time a physiological function of B. abortus Omp19. This activity enables Brucella to better thrive in the harsh gastrointestinal tract, where protection from proteolytic degradation can be a matter of life or death, and afterwards invade the host and bypass intracellular proteases to establish the chronic infection.